"\\frac{dy}{dx} = ye^{-x^2}"
"\\frac{dy}{y} = e^{-x^2}dx"
"\\int\\frac{du}{y}=\\int e{^{-x^2}}dx"
But "\\int e^{-x^2}dx" is a non elementary integral. We can express it as a power series
"e^{-x^2}= 1 - \\frac{x^2}{1!}+\\frac{x^4}{2!}-\\frac{x^6}{3!} +\\frac{x^8}{4!}-.."
We can approximate it as
"e^{-x^2}= 1 - \\frac{x^2}{1!}+\\frac{x^4}{2!}-\\frac{x^6}{3!}"
So differential equation transforms to
"\\int\\frac{du}{y}=\\int" "(1 - \\frac{x^2}{1!}+\\frac{x^4}{2!}-\\frac{x^6}{3!})dx"
=>ln|y| = "x - \\frac{x^3}{3}+\\frac{x^5}{10}-\\frac{x^7}{42} + C"
By initial condition y(5)=1
0 = "5 - \\frac{5^3}{3}+\\frac{5^5}{10}-\\frac{5^7}{42} + C"
C = 1584.286
So ln|y| = "x - \\frac{x^3}{3}+\\frac{x^5}{10}-\\frac{x^7}{42} + 1584.286"
=> y = "e^{(x - \\frac{x^3}{3}+\\frac{x^5}{10}-\\frac{x^7}{42} + 1584.286)}"
This is the explicit solution of the given differential equation
"\\mathbf ALTERNATIVELY"
"\\frac{dy}{dx} = ye^{-x^2}"
=> "\\frac{dy}{y} = e^{-x^2}dx"
=> "\\int\\frac{du}{y}=\\int e{^{-x^2}}dx"
As "\\int e{^{-x^2}}dx" is not an elementary integral, we will express it as error function
=> ln|y| = ("\\frac{\\sqrt\u03c0}{2}" ) erf(x) + C1, C1 is integration constant
Where erf(x) = "\\int_0^x e{^{-t^2}}dt"
So y = "e^{ (\\frac{\\sqrt\u03c0}{2}) erf(x) + C_1}"
=> y = C"e^{ (\\frac{\\sqrt\u03c0}{2}) erf(x)}"
By initial condition y (5)=1
1 = C"e^{ (\\frac{\\sqrt\u03c0}{2}) erf(5) }"
C = "e^{ -(\\frac{\\sqrt\u03c0}{2}) erf(x) }"
So y = "e^{ (\\frac{\\sqrt\u03c0}{2}) erf(x) - (\\frac{\\sqrt\u03c0}{2}) erf(5) }"
=> y = "e^{ (\\frac{\\sqrt\u03c0}{2}) [erf(x) - erf(5) ]}"
This is the explicit solution of the given differential equation
Comments
Leave a comment